Reinterpretation of Malvinoconulariacahuanotensis (Braniša and Vanek) from the Devonian Altiplano and Western Andean Cordillera, Bolivia, South America (Ameghiniana, 2013)
Abstract. The holotype of Malvinoconulariacahuanotensis (Braniša and Vanek) (Devonian, Bolivia), the type species of the monospecific genus Malvinoconularia Babcock etal., is redescribed and refigured. M.cahuanotensis exhibits several gross morphological features that together are uniquely shared with Reticulaconulariabaini (Babcock and Feldmann). In both taxa, the transverse ribs are nodose, the interspaces bear longitudinal ridges (bars or crests) that are collinear (line up) across the transverse ribs, and the longitudinal centerline (midline) of the faces is marked by a subdued ridge. Additionally, the two species may also be similar in the anatomy and external ornament of the corner sulcus. The slightly undulose geometry of the transverse ribs of M. cahuanotensis also is exhibited by certain specimens of Reticulaconularia; however, whether this feature is primary or taphonomic in origin is unclear at present. Together, these similarities suggest that the genus Malvinoconularia probably is a junior synonym of the genus Reticulaconularia.Resumen. REINTERPRETACIÓNDE MALVINOCONULARIA CAHUANOTENSIS (BRANIŠAY VANEK) DEL DEVÓNICODE BOLIVIA, AMERICA DEL SUR. El holotipo de Malvinoconulariacahuanotensis (Braniša y Vanek) (Devónico, Bolivia), la especie tipo del género Malvinoconularia Babcock etal., es reinterpretado y refigurado. M. cahuanotensis exhibe varios rasgos morfológicos que en conjunto son compartidos únicamente con Reticulaconulariabaini (Babcock y Feldmann). En ambos taxones las costillas transversas son nodosas, los interespacios poseen aristas longitudinales (barras o crestas) que son colineares a las costillas transversas, y las caras presentan una pequeña elevación externa sobre su línea media. Además, estas especies parecen ser similares en la anatomía y ornamentación externa del surco marginal. La geometría suavemente ondulada de las costillas de M. cahuanotensis es también exhibida por ciertos especímenes de Reticulaconularia, aunque aún no es claro si esta característica es primaria o tafonómica en su origen. En conjunto, estas similitudes sugieren que Malvinoconularia es un sinónimo junior de Reticulaconularia.